Determination of Loyalty Through Mediation of Patient Satisfaction at Indriati Boyolali Hospital - Restu Wijang Setiabudi; Sudarwati; Ida Aryati Diyah Purnomo Wulan (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
This study aims to reveal the influence between CRM, SST, customer satisfaction and loyalty variables with the mediation of patient satisfaction in outpatients of Indriati Boyolali Hospital. This research used a quantitative descriptive approach—data collection using questionnaires, observations and documentation. The research location was Indriati Boyolali Hospital which is located at Jl. Raya Boyolali-Semarang No.KM. 02, Mojosngopermai, Mojosongo, Boyolali District, Boyolali Regency, Central Java. In conducting this study, the time needed was six months, and the sample of respondents was 230 outpatients at Indriati Boyolali Hospital. Some of the following conclusions Customer relationship marketing affects patient loyalty. Customer Relationship Marketing affected Patient Satisfaction. Self Service Technology affected Patient Loyalty, Self Service Technology affected Patient Satisfaction, Patient Satisfaction affected Patient Loyalty, and Patient Trust as an Intervening Variable did not affect patient loyalty. Customer Relationship Marketing affected patient commitment with patient satisfaction mediation. Self Service Technology affected patient loyalty with patient satisfaction mediation.